Comparative transcriptome analysis of Peromyscus leucopus and C3H mice infected with the Lyme disease pathogen - Gaber, Alhussien M.; Mandric, Igor; Nitirahardjo, Caroline; Piontkivska, Helen; Hillhouse, Andrew E.; Threadgill, David W.; Zelikovsky, Alex; Rogovskyy, Artem S. (Frontiers in Cellular and Infection Microbiology, 2023)
Lyme disease (LD), the most prevalent tick-borne disease of humans in the Northern Hemisphere, is caused by the spirochetal bacterium of Borreliella burgdorferi (Bb) sensu lato complex. In nature, Bb spirochetes are continuously transmitted between Ixodes ticks and mammalian or avian reservoir hosts. Peromyscus leucopus mice are considered the primary mammalian reservoir of Bb in the United States. Earlier studies demonstrated that experimentally infected P. leucopus mice do not develop disease. In contrast, C3H mice, a widely used laboratory strain of Mus musculus in the LD field, develop severe Lyme arthritis. To date, the exact tolerance mechanism of P. leucopus mice to Bb-induced infection remains unknown. To address this knowledge gap, the present study has compared spleen transcriptomes of P. leucopus and C3H/HeJ mice infected with Bb strain 297 with those of their respective uninfected controls. Overall, the data showed that the spleen transcriptome of Bb-infected P. leucopus mice was much more quiescent compared to the infected C3H mice. To date, the current investigation is one of the few that have examined the transcriptome response of Bb natural reservoir hosts to Bb infection. Although the experimental design of this study significantly differed from those of two previous investigations, the collective results of the current and published studies have consistently demonstrated very limited transcriptomic responses of different reservoir hosts to the persistent infection of LD pathogens.